Self-reported Perceptions of Weight and Eating Behavior of School Children in Sunderland, England - McInnes, Alison; Blackwell, David (Frontiers in Public Health, 2017)
The main aim of this study was to determine the self-reported perceptions of weight and eating behaviors of school age children in Sunderland in the North East of England. The results presented are derived from data collected by a Health Related Behaviour Survey developed by Schools and Students Health Education Unit (SHEU) at Exeter University and this study is based on analysis of the data set collected for Sunderland. A total of 12,213 pupils from nine secondary schools completed the questionnaire biennially from 1996 to 2012. The sample included 12 and 13 year olds and 14 and 15 year olds. A variety of health and social issues related to perceptions of weight and eating behaviors were determined. Trends related to these issues were identified according to age and and gender of respondents and differences between the groups were highlighted. From the analysis some interesting findings relating to eating patterns and weight perception amongst young people were ascertained. Females of both age groups reported a greater desire to lose weight than their male counterparts. The percentage of school children who reported having breakfast at home has increased progressively, as have those having lunch at school. The percentage of school children purchasing lunch from takeaway outlets has dramatically decreased. This is pleasing since health policy of limiting take out provision is high on government agenda and these trends can be used by policy makers to focus on continuing to improve school meals. The findings partly support other national data, but also contradict the widely held beliefs around food and obesity in the North East of England.